2013
DOI: 10.1155/2013/264387
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Mechanisms of Cardioprotection Mediated by Thyroid Hormones

Abstract: Heart failure represents the final common outcome in cardiovascular diseases. Despite significant therapeutic advances, morbidity and mortality of heart failure remain unacceptably high. Heart failure is preceded and sustained by a process of structural remodeling of the entire cardiac tissue architecture. Prevention or limitation of cardiac remodeling in the early stages of the process is a crucial step in order to ameliorate patient prognosis. Acquisition of novel pathophysiological mechanisms of cardiac rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 90 publications
(88 reference statements)
0
29
0
Order By: Relevance
“…Furthermore, clinical studies have shown that levels of T3 have a positive correlation with ejection fraction (EF%) in ST-elevation myocardial infarction (STEMI) patients at 48 h from the index event (22). Consistently, treatment of Low-T3S exerts cardioprotective effects in both humans and animal models and may be a novel option for treatment of cardiac disease (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Experimental Protocolmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, clinical studies have shown that levels of T3 have a positive correlation with ejection fraction (EF%) in ST-elevation myocardial infarction (STEMI) patients at 48 h from the index event (22). Consistently, treatment of Low-T3S exerts cardioprotective effects in both humans and animal models and may be a novel option for treatment of cardiac disease (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Experimental Protocolmentioning
confidence: 92%
“…Decreased levels of the bioactive TH T3 are frequently observed in the post-I/R setting, and there is a long-lasting dilemma as to whether this abnormality needs correction. Increasing experimental evidence suggests that THs display multiple functions to induce cardioprotection from I/R injury (26). We recently reported a key role of THs in limiting postischemic cardiomyocytes death.…”
Section: Th Administration Exerts a Modulatory Action On Profibrotic mentioning
confidence: 97%
“…In a study by Nicolini et al, it is clearly stated that low Thyroid hormone is not simply a consequence of cardiac disease evolution but a permissive state that favours adverse cardiac remodelling and failure. [7] Correlation of fT3 with EF -an indicator of myocardial function, yielded a p value of 0.099, though close to significance but not. There was a clear increase in EF with increase in fT3 levels thus emphasizing the cardioprotective mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, MI being an inflammatory condition causes a reduction in thyroid levels and this reduced thyroid level worsens the pathological cardiac remodelling, further worsening the condition of the heart. [7] The assessment of left ventricular function following acute myocardial infarction is important from a prognostic point of view. Therapeutic studies have used global ejection fraction (EF) as assessed by either radionuclide ventriculography (RNV), echocardiographic LVEF alone or a combination of any of RNV, echocardiographic LVEF, ventricular angiographic LVEF as markers for LV dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…However, this intervention was both invasive and impractical to apply, and non-invasive approaches for protecting the heart were sought such as exposure to a brief limb ischemia (remote IPC) (25), pharmacological agents, hyperoxic environment, exercise and so on. In experimental IR injury models, the protective effect of a wide range of hormones, including oxytocin (34), prolactin (26), estrogen (4), thyroid hormone (33), and endogenous substances, including NO (23), and heat shock proteins (14) including heme oxygenase-1 (24) has been shown. Due to substantial changes in the factors involved in the regulation of cardiovascular function during lactation, the purpose of the present study was to explore whether lactation may protect the heart against ischemia reperfusion (IR) injury in an in vivo rat model.…”
mentioning
confidence: 99%